Motivating and Engaging Students: Reflections on Gamifying Online Courses Through a Digital Badging Program - Thomas D. Dyer; R. Jacob Aroz (Journal of Scholarly Engagement)
The purpose of this reflective critique was to explore faculty approaches to engage and motivate students while promoting community and building skills in the online classroom. One of the primary benefits of this critique is to bring focus to this often-overlooked aspect of gamification, students’ unsolicited feedback addressing the feasibility of digital badges in the online classroom. This reflective critique was supported by the theoretical framework of Lev Vygotsky and the theory of social development. We focused explicitly on the constructs of digital badging and gamification. We analyzed unsolicited student comments, which were useful in revealing additional information about student perceptions of a digital badging program. The implications of this type of analysis have value in its ability to reveal patterns in previously unused data that can be used to reflect on classroom practices. Data analysis resulted in four themes addressing the digital badging program: (a) digital badges motivate students in the online classroom, (b) digital badges promote community in the online classroom, (b) digital badges reward student participation in the online classroom, and (c) digital badges encourage skill development in the online classroom. While there are challenges in creating a digital badging program, most notably time, positive student and instructor experiences encouraged us to move forward.